Evaluative Language Maintenance and Shift on Vice-Presidential Candidates Reportage: Translation Analysis of ‘The Conversation’ Political News - Ahmad Zakki Maulana; Mangatur Rudolf Nababan; Riyadi Santosa (Script Journal: Journal of Linguistics and English Teaching, 2020)
Background: This paper seeks to shed some light concerning on evaluative language maintenance and shift at translation phenomenon of online news. Though this translation issue is frequently discussed in academic discourse, little has been concerned on comprehending to what extent the evaluation used in political news has been retained of shifted in their target texts. Methodology: Three political news articles published on ‘The Conversation’ online media were selected for the analysis. For doing so, appraisal system and translation technique theory-based concepts were adopted to guide the analysis as well as the discussion. We employed a noteworthy move in terms of data collection technique, that is focus-group discussion by involving a number of experts who are engaged in the field of linguistics and translation studies. Findings: This research findings can be understood as evaluative language maintenance dominating the data compared to translation shift. Translators attempted to bridge Indonesian readers by rendering some ideologically news, with the aim of knocking language distance down between English and Indonesian texts. Meanwhile, a plenty of translation techniques encourage translator awareness to take position upon rendering ideological news, in case of retaining, altering, as well as omitting the constructed meanings. Conclusion: It is pivotal, as a consequence, to increase news translators’ awareness of understanding attitude constructed in political news. Otherwise, there will be reframing phenomena as the cause of translators’ intervention depriving readers’ rights to understand mass media attitude. Keywords: evaluative language; translation; political news